Exploring Synergies: Tailoring Electrical Conductivity in Novel Corn Starch and Natural Rubber Polymer Composites through Varied Carbon Additives - Fiqri, Miftahul; Humaidi, Syahrul; Frida, Erna; Estananto, Estananto (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Conductive polymer composites were synthesized using a crosslinking method, enhancing conductivity through the incorporation of carbon additives. Non-conductive natural polymers, corn starch, and natural rubber were blended with carboxymethyl cellulose (CMC) as a crosslinking agent, enhancing polymer bonding. CMC also served as a compatibilizer, improving corn starch properties. Glycerol acted as a plasticizer, enhancing flexibility and processability. Addition of carbon nanotube (CNT), graphite, and carbon foam yielded low-density materials, with carbon foam providing optimal porosity. The crystalline properties mirrored the added conductive carbon, while the chemical structure remained unchanged. At 0.1 Hz, electrical conductivity varied: 1.192 x 10-7 S.cm-1 (no carbon), 6.123 x 10-4 S.cm-1 (CNT), 7.656 x 10-4 S.cm-1 (graphite), and 3.134 x 10-2 S.cm-1 (carbon foam). Graphite incorporation demonstrated an electrical conductivity of 7.838 x 10-4 S.cm-1. The introduced carbon additives facilitated a conductive pathway in corn starch-based polymer composites, elevating material conductivity.